The Impact of Immigration on Firm-Level Offshoring - Olney, William W.; Pozzoli, Dario (The Review of Economics and Statistics, 2021)
This paper studies the relationship between immigration and offshoring by examining whether an influx of foreign workers reduces the need for firms to relocate jobs abroad. Using a Danish natural experiment and their employer-employee matched data set covering the universe of workers and firms (1995–2011), our findings show that an exogenous influx of immigrants into a municipality reduces firm-level offshoring at both the extensive and intensive margins. While the multilateral relationship is negative, a subsequent bilateral analysis shows that immigrants have connections in their country of origin that increase the likelihood that firms offshore to that particular foreign country.